2007
DOI: 10.1007/s12010-007-8093-z
|View full text |Cite
|
Sign up to set email alerts
|

Production of Cyclodextrins by CGTase from Bacillus clausii Using Different Starches as Substrates

Abstract: Cyclodextrins (CDs) are cyclic oligasaccharides composed by D-glucose monomers joined by alpha-1,4-D glicosidic linkages. The main types of CDs are alpha-, beta- and gamma-CDs consisting of cycles of six, seven, and eight glucose monomers, respectively. Their ability to form inclusion complexes is the most important characteristic, allowing their wide industrial application. The physical property of the CD-complexed compound can be altered to improve stability, volatility, solubility, or bio-availability. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
27
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(28 citation statements)
references
References 31 publications
(38 reference statements)
1
27
0
Order By: Relevance
“…A selective purification step is, thus, required to obtain pure α-CD, β-CD, or γ-CD, through the use of complexing agents during CD synthesis and the variation in solubility of the different CDs to allow selective precipitation (Matioli et al 2000; Lee and Kim 1992; Son et al 2008). The source of CGTase is the key factor in the type of CDs produced (Table 1), along with reaction parameters such as the type of starch used, the buffer composition, reaction temperature, and pH (Qi et al 2004; Kamaruddin et al 2005; Alves-Prado et al 2008). …”
Section: Productionmentioning
confidence: 99%
See 1 more Smart Citation
“…A selective purification step is, thus, required to obtain pure α-CD, β-CD, or γ-CD, through the use of complexing agents during CD synthesis and the variation in solubility of the different CDs to allow selective precipitation (Matioli et al 2000; Lee and Kim 1992; Son et al 2008). The source of CGTase is the key factor in the type of CDs produced (Table 1), along with reaction parameters such as the type of starch used, the buffer composition, reaction temperature, and pH (Qi et al 2004; Kamaruddin et al 2005; Alves-Prado et al 2008). …”
Section: Productionmentioning
confidence: 99%
“…G-825-6γ(Hirano et al 2006)Alkalophilic Bacillus sp. I-5β(Shim et al 2004) Anaerobranca gottschalkii α(Thiemann et al 2004) Bacillus circulans 8β(Nitschke et al 1990) Bacillus circulans 251β(Lawson et al 1994) Bacillus circulans A11β(Rimphanitchayakit et al 2005) Bacillus circulans DF 9Rα/β(Marechal et al 1996) Bacillus clarkii 7384γ(Takada et al 2003) Bacillus clausii E16 a β(Alves-Prado et al 2008) Bacillus firmus 290-3β/γ(Englbrecht et al 1988) Bacillus firmus 7B a β(Moriwaki et al 2007) Bacillus firmus NCIM 5119 a β(Gawande et al 1999) Bacillus firmus no. 37 a β(Matioli et al 2001) Bacillus licheniformis α/β(Hill et al 1990) Bacillus macerans b α(Takano et al 1986) Bacillus megaterium a β(Pishtiyski et al 2008) Bacillus obhensis β(Sin et al 1991) Bacillus sp.…”
Section: Productionmentioning
confidence: 99%
“…Earlier reports have shown that CGTase thermostability is enhanced in the presence of its substrate, products, and calcium ions [20,29,32]. Therefore, the influence of these additives on the thermostability of Amphibacillus sp.…”
Section: Resultsmentioning
confidence: 99%
“…However, increasing of the reaction temperature to 75 °C caused rapid decrease of the relative enzyme activity to 26.4%. Temperature optima in the range of 55–65 °C have been previously reported for CGTases from various alkaliphiles [20,23,27,29,31]. However, CGTase from thermophilic bacteria usually shows optimal activity at higher temperatures [28,32].…”
Section: Resultsmentioning
confidence: 99%
“…Because of their ability to form inclusion complexes with many organic molecules, CDs and their derivatives have become increasingly useful in food, pharmaceuticals and cosmetics industries, analytical chemistry, agriculture, and biotechnology. The physical properties of the CD-complexed compound can be altered to improve stability, volatility, solubility, or bioavailability [5]. In the last decade, a few interesting large-ring CDs showing novel structural features were isolated and characterized, but α-, β-, and γ-CDs are the most extensively studied and used products [6].…”
Section: Introductionmentioning
confidence: 99%